How changes in river geometry impact flood hazard in Brazil - Alondra Beatriz Alvarez Perez; Fernando Grison; Vinícius B. P. Chagas; Marcus Suassuna Santos; Pedro Luiz Borges Chaffe (Hydrological Sciences Journal, 2026)

Hydrogeomorphological controls on saline and hypersaline shallow lakes in the Pampean Plain (Argentina) under sub-humid conditions - R. Acosta; E. Carol; M. P. Alvarez (Sustainable Water Resources Management, 2026)

On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

The MIREN Road Survey Database: Standardized Vegetation Sampling to Advance Our Understanding of Biodiversity Responses in Mountain Systems Across the Globe - Sylvia Haider; Jonas J. Lembrechts; Jake Alexander; Vincent Ralph Clark; Lisa J. Rew; Meike Buhaly; Marc Achermann; Alla Aleksanyan; Alisa Alvarez; Marco Andrello; José R. Arévalo; Valeria Aschero; et al. (Global Ecology and Biogeography, 2026)
Motivation The database initiated by the Mountain Invasion Research Network (MIREN) is one of the few globally implemented standardized vegetation surveys in mountains. The focus is on collecting plant species occurrences at 5‐year intervals along and adjacent to mountain roads spanning elevational gradients, with the goal of providing critical information about the ongoing spread of non‐native plants and the potential impacts of climate and human‐caused disturbance in the form of road infrastructure on mountain vegetation. Main Types of Variables Contained To date, the database contains almost 170,000 georeferenced records of plant species. Overall, 6854 vascular plant species were observed in 3364 plots across 25 regions, with many of these plots being revisited every 5 years. Each plot is identified by its coordinates, elevation and distance to the road. The status of each individual species (native, non‐native or unknown) is determined in accordance with regional databases. Spatial Location and Grain Plant species were surveyed at 20 sample sites, placed at regular elevational intervals along each mountain road, with typically three roads selected per region. Each sample site is subdivided into three 2 m × 50 m plots, one parallel to the road and two perpendicular to it, extending into adjacent vegetation. The 25 studied regions cover all continents except Antarctica. Time Period and Grain Data were collected between 2007 and 2023, with surveys being repeated at 5‐year intervals in a subset of regions. Three regions include four time‐steps, while seven and three regions were sampled three times or twice, respectively. In most regions, long‐term monitoring is ongoing. Major Taxa and Level of Measurement All vascular plant species. Software Format Data are available through a .csv file on Zenodo ( https://doi.org/10.5281/zenodo.15749536 ).

A bromoform-based Investigational Veterinary Product reduced methane emissions and increased feed conversion efficiency of yearling steers when delivered via drinking water - W.L. de Souza; S.P. Quigley; A.L. Bates; R.J. Batley; M.A.O. Castro; J.M. Gasparina; O. Gillies; P. Guerreiro; P.S. Alvarez-Hess; M.J. Auldist; S. Jacques; R. Tognelli; et al. (Animal Feed Science and Technology, 2026)

Some further insights into oxfendazole broad anthelmintic spectrum: Flukicidal efficacy at a high dose in sheep - P. Soler; R. Herrera; L. Moreno; J.P. Lirón; C. Canton; C. Lanusse; L. Alvarez; L. Ceballos; M. Larroza (Veterinary Parasitology, 2026)

Microbial and chemical stability of commercial kombucha after thermal processing - Tobías Moccia; Carolina Antuña; Andrea Trochine; Lucía P. Alvarez (Food Bioscience, 2026)

Genetic testing for hereditary breast and ovarian cancer in the Murcian population using a comprehensive NGS panel - Y. Mestre Terkemani; L. Rosado Jiménez; A. García Aliaga; M. D. Sarabia Meseguer; M. Marín Vera; J. A. Macías Cerrolaza; P. Sánchez Henarejos; M. R. García Hernández; M. Zafra Poves; B. Alvarez Abril; E. García Torralba; C. B. López Sánchez; et al. (Familial Cancer, 2026)

Mermaids in pools: Ex-situ conservation as a cornerstone for sirenian management worldwide - D.N. Castelblanco-Martínez; E.A. Ramos; A. Alvarez-Aleman; L. von Fersen; R.S. Amaral; F.L.N. Attademo; J.C.G. Borges; L.J. Cabrias-Contreras; D. Caicedo-Herrera; T. Calleson; V.L. Carvalho; A. Dávila-Peñaloza; et al. (Journal for Nature Conservation, 2026)

Microalgae, sunlight, and starch: low cell concentration is optimal for outdoor production under nutrient stress - A. Six; P. Chambonnière; P. Alvarez; S. Fon-Sing; C. Lancelon-Pin; J.-L. Putaux; J.-F. Sassi; Y. Li-Beisson; G. Fleury (Bioresource Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Germline MLH1 c.-42 C > T is a likely pathogenic variant predisposing to a reduced-penetrance/modified Lynch syndrome phenotype featuring MLH1-methylated cancers - Daniel D. Buchanan; Rocio Alvarez; Khalid Mahmood; Mark Clendenning; Peter Georgeson; Romy Walker; Julia Como; Susan G. Preston; Sharelle Joseland; Kimia Mohammadsaeedi; Francesca Aguirre; Lisa Zhou; et al. (Familial Cancer, 2026)
The germline MLH1 c.-42 C > T (rs41285097) promoter variant has been identified in cases with MLH1-deficient colorectal or endometrial cancers but remains a variant of uncertain significance. Genetic testing identified two new MLH1 c.-42 C > T index cases from Australia and the USA. Clinicopathologic and molecular characterisation of tumour and non-neoplastic tissues was performed to investigate the potential mechanism of pathogenesis of this variant. The male Australian proband developed MLH1-deficient, BRAF p.V600 wildtype, CIMP-negative colon cancer at 61 years. MLH1 monoallelic methylation and a somatic pathogenic mutation, MLH1 c.1122_1126dup p.Asp376Valfs*27, were identified in his tumour. Droplet digital PCR (ddPCR) detected mosaic MLH1 methylation in normal colonic mucosa adjacent to the cancer (3.7%) with lower levels in blood (0.07%) and saliva (0.09%). The USA proband developed MLH1-deficient endometrial cancer at 38 years with MLH1 monoallelic methylation and loss-of-heterozygosity of the wildtype c.-42 C allele. No evidence of MLH1 methylation was found by ddPCR in normal tissues. MLH1 c.-42 C > T heterozygous relatives from both families had either no or extremely low levels of MLH1 methylation within blood or saliva. Allelic expression from MLH1 c.-42T was reduced to 70% relative to the wild-type allele in saliva from three heterozygotes. Three additional pedigrees were identified from the Colon Cancer Family Registry. Evaluation of combined multifactorial data from pooled informative index cases supports reclassification of this variant as “likely pathogenic” according to current ACMG/AMP mismatch repair gene-specific guidelines, though with likely reduced penetrance and/or modified phenotype. These findings highlight the clinical importance of identifying MLH1 c.-42 C > T to inform cancer risk management.

Climate-induced shifts in swordfish spawning habitat in the Western Mediterranean - M.P. Tugores; A.P. Torres; P. Reglero; M. Martín; R. Balbín; J. Tintoré; D. Alvarez-Berastegui (Progress in Oceanography, 2026)

Superchilling storage reduces the growth and diversity of bacterial communities associated with Atlantic salmon (Salmo salar) fillets - P. Collin; M. Darsonval; O. Rué; F.T. Ndoye; G. Alvarez; F. Dubois-Brissonnet (Food Research International, 2026)

Short-term high-intensity resistance training: a feasibility study on pulmonary, immune and physical-functional fitness benefits for older adults with metabolic syndrome - Juliana de Melo Batista dos Santos; Guilherme Eustáquio Furtado; Eviton Correa-Sousa; Maysa Alves Rodrigues Brandao-Rangel; Manoel Carneiro Oliveira-Junior; Katielle Rodrigues da Silva Cardoso; Mariana Alvarez de Souza; Francisco Rodrigues; Patricia Coelho; Luís Vicente Franco de Oliveira; André Luís Lacerda Bachi; Luciana Malosa Sampaio Jorge; et al. (European Journal of Applied Physiology, 2026)
The incidence of metabolic syndrome (MetS) is rising rapidly, particularly among older adults, and is associated with comorbidities that impair respiratory and immune functions. Physical exercise has proven effective in mitigating the adverse effects of both aging and MetS. However, evidence on the impact of high-intensity resistance training (HIRT) on the respiratory and immune systems in older adults with MetS remains limited. This study aimed to evaluate the effects of HIRT on respiratory function, skeletal muscle strength, and immune modulation in older adults with MetS, highlighting its potential as a complementary therapeutic approach. A total of 43 older adults with MetS were enrolled and divided into two groups: a HIRT intervention group (n = 23; mean age 66.71 ± 4.98 years) and a non-exercising control group (n = 20; mean age 66.91 ± 5.26 years). The HIRT protocol involved twice-weekly sessions (10 total) over 5 weeks, performed at 80–90% of one-repetition maximum. Results showed that HIRT significantly improved lung mechanics (R5Hz, R20Hz, Z5Hz, X5Hz), peripheral muscle strength, and both maximal expiratory and inspiratory pressures. Furthermore, HIRT increased anti-inflammatory and anti-fibrotic cytokines in sputum (klotho, IL-10, adiponectin) and serum (klotho, relaxin-1, relaxin-3, IL-10), while reducing pro-inflammatory cytokines in sputum (IL-6, TNF-α) and serum (IL-1ra, IL-6, TNF-α, leptin). A decrease in total leukocyte, neutrophil, lymphocyte, and monocyte counts was also observed. In conclusion, HIRT effectively mitigates the effects of MetS on respiratory, muscular, and immune functions in older adults and may be recommended as a complementary strategy for managing MetS in this population.

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

Fouling-release coatings enhance Acropora loripes coral spat survival by limiting algal competition on seeding devices - Jose Montalvo-Proano; Mariana Alvarez-Noriega; Florita Flores; Andrea Severati; Andrew P. Negri (Frontiers in Marine Science, 2025)
Early post-settlement mortality is a major bottleneck in larval-based coral restoration, largely driven by competitive overgrowth from benthic fouling organisms. Non-biocidal fouling-release coatings (FRCs) may reduce fouling pressure and enhance spat survival, but their efficacy in situ remains poorly quantified. We evaluated whether a commercial FRC could reduce benthic fouling and improve survival of Acropora loripes spat on a mid-shelf Great Barrier Reef. Larvae were settled onto ceramic seeding devices containing either FRC-treated or untreated (control) cores. Devices were deployed on the reef and monitored for fouling cover and spat survival over 46 weeks (~12 months). Relationships between spat survival, fouling, and benthic community composition were assessed. Fouling was substantially lower on FRC-treated devices, with only 25% fouling cover, compared to near-total overgrowth on controls. Importantly, spat survival remained consistently higher on FRC devices (68%) compared to controls (59%) at 46 weeks. Spat survival was negatively associated with device fouling, independent of immediate benthic community composition. This study provides the first in situ mechanistic evidence that FRCs indirectly enhance coral spat survival by mitigating competitive fouling pressure during the critical early growth period. Although the greatest benefit occurred in the first six months, fouling protection persisted throughout the deployment, suggesting that FRCs could provide a scalable solution to improve restoration outcomes. Integration of FRCs into seeding device design represents a promising strategy to support large-scale coral reef restoration under ongoing climate stress.

Implementation of generalised retention models in RPLC using serially coupled columns: a study based on lemon balm extracts - P. Peiró-Vila; A.J. Mateu-Llácer; M.C. García-Alvarez-Coque; J.R. Torres-Lapasió (Analytica Chimica Acta, 2025)

MLH1 c.27G>A (p.Arg9=) is a synonymous likely/pathogenic variant underlying variably mosaic constitutional MLH1 methylation in Lynch syndrome - Rocio Alvarez; Paula Climent-Cantó; GiWon Shin; Francesca Paola Aguirre; Lisa Zhou; Dennis J. Hazelett; Brent K. Larson; Covadonga Vara; Gabriel Capellá; Víctor Lorca Castellanos; Pilar Garre Rubio; Françoise Desseigne; et al. (Familial Cancer, 2025)

Extracellular vesicle isolation and characterization from bottlenose dolphin’s (Tursiops truncatus) breath - V. Moccia; C. Centelleghe; A. Zendrini; G. Pesce; E. Alvarez; E. Esposti; A. Radeghieri; P. Bergese; S. Mazzariol; V. Zappulli (Journal of Comparative Pathology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effective novel and conventional technologies for decontamination of aflatoxin B1 in foods: a review - Diego Fernando García-Ramón; Heber P. Cornelio-Santiago; Edgar Norabuena; Liliana Sumarriva; Hermelinda Alvarez-Chancasanampa; Marlitt Naupay Vega; Alejandrina Sotelo-Méndez; Luis Alfredo Espinoza-Espinoza; Lucia R. Pantoja-Tirado; Sara H. Gonzales-Agama; Esmila Y. Chavarría-Marquez; Cesar Raul Castro-Galarza (Mycotoxin Research, 2025)

How well CMIP6 models simulate key boundary conditions affecting South American climate? Insights for regional modeling efforts - Paola A. Arias; Isabel C. Correa; Lluís Fita; J. Alejandro Martínez; Camila Alvarez-Garreton; Lincoln M. Alves; Juan P. Boisier; Lenin Campozano; Jhan-Carlo Espinoza; Clementine Junquas; Marta Llopart; Anna A. Sörensson (Climate Dynamics, 2025)
South America is a large continent with a wide diversity of weather and climate features, including tropical, subtropical and extratropical regimes interacting within a complex landscape. Simulations by global climate models, as well as their downscaling through regional circulation models or statistical methods, are important tools, particularly when assessing the impacts of climate change in the continent. This work evaluates 57 models of the sixth phase of the Coupled Model Intercomparison Project (CMIP6) in their simulation of various spatial patterns and circulation features over South America. Our evaluation aims to provide useful input for the selection of climate models to force regional simulations in South America. Therefore, we focus on spatial fields that are relevant for regional simulations, such as horizontal winds, sea level pressure, sea surface temperature (SST), and moisture and energy fluxes across the domain boundaries. Additionally, we evaluated different circulation features influencing the regional climate of South America that have not been widely evaluated in these models. Several indices are studied to assess the main low-level and upper-level continental-scale circulation patterns, the regional Walker and Hadley cells, the subtropical highs and the boundary SST patterns. Our results show that no single model performs best across all evaluated features, highlighting the importance of in-depth model evaluation for the region concerning the features of interest.

Genome-wide analyses provide insights into genetic variation, phylo- and co-phylogenetic relationships, and biogeography of the entomopathogenic nematode genus Heterorhabditis - Ricardo A.R. Machado; Arthur Muller; Alexandre Hiltmann; Aashaq Hussain Bhat; Vladimír Půža; Antoinette P. Malan; Carlos Castaneda-Alvarez; Ernesto San-Blas; Larry W. Duncan; David Shapiro-Ilan; Javad Karimi; Lalramliana; et al. (Molecular Phylogenetics and Evolution, 2025)

Metro Manila households’ willingness to pay for renewable energy as a climate change mitigation measure: a CVM study - Rosalina Palanca-Tan; Masahiro Sugiyama; Daniel del Barrio Alvarez; Gem B. Castillo; Nelson Matthew P. Tan (Sustainability Science, 2025)

Investigation of nuclide inventory of cladding material irradiated in the Goesgen PWR core - R. Dagan; T. König; M. Herm; F. Alvarez; E. Dorval; S. Häkkinen; E. Vlassopoulos; A. Shama; A. Smaizys; P. Schillebeeckx (Annals of Nuclear Energy, 2025)

Global retention model based on multisample system parameters for optimising chromatographic fingerprints of medicinal plants - P. Peiró-Vila; M.C. García-Alvarez-Coque; J.R. Torres-Lapasió (Analytica Chimica Acta, 2025)

High frequency of plastic ingestion in procellariiform seabirds (albatrosses, petrels and shearwaters) in the Southwest Atlantic Ocean - Luciana Gallo; Patricia P. Serafini; Ralph E.T. Vanstreels; Leandro L. Tamini; Cristiane K.M. Kolesnikovas; Alice Pereira; Tatiana Neves; Gabriel D. Nascimento; Lucas S. Rodriguez Pirani; A. Lorena Picone; Rosana M. Romano; C. Karina Alvarez; et al. (Marine Pollution Bulletin, 2024)

Osteosarcoma cells exhibit functional interactions with stromal cells, fostering a lung microenvironment conducive to the establishment of metastatic tumor cells - Matías J. P. Valenzuela Alvarez; Luciana M. Gutierrez; Juan M. Bayo; María J. Cantero; Mariana G. Garcia; Marcela F. Bolontrade (Molecular Biology Reports, 2024)

Promoting best practices in ocean forecasting through an Operational Readiness Level - E. Alvarez Fanjul; S. Ciliberti; J. Pearlman; K. Wilmer-Becker; P. Bahurel; F. Ardhuin; A. Arnaud; K. Azizzadenesheli; R. Aznar; M. Bell; L. Bertino; S. Behera; et al. (Frontiers in Marine Science, 2024)
Predicting the ocean state in a reliable and interoperable way, while ensuring high-quality products, requires forecasting systems that synergistically combine science-based methodologies with advanced technologies for timely, user-oriented solutions. Achieving this objective necessitates the adoption of best practices when implementing ocean forecasting services, resulting in the proper design of system components and the capacity to evolve through different levels of complexity. The vision of OceanPrediction Decade Collaborative Center, endorsed by the UN Decade of Ocean Science for Sustainable Development 2021-2030, is to support this challenge by developing a “predicted ocean based on a shared and coordinated global effort” and by working within a collaborative framework that encompasses worldwide expertise in ocean science and technology. To measure the capacity of ocean forecasting systems, the OceanPrediction Decade Collaborative Center proposes a novel approach based on the definition of an Operational Readiness Level (ORL). This approach is designed to guide and promote the adoption of best practices by qualifying and quantifying the overall operational status. Considering three identified operational categories - production, validation, and data dissemination - the proposed ORL is computed through a cumulative scoring system. This method is determined by fulfilling specific criteria, starting from a given base level and progressively advancing to higher levels. The goal of ORL and the computed scores per operational category is to support ocean forecasters in using and producing ocean data, information, and knowledge. This is achieved through systems that attain progressively higher levels of readiness, accessibility, and interoperability by adopting best practices that will be linked to the future design of standards and tools. This paper discusses examples of the application of this methodology, concluding on the advantages of its adoption as a reference tool to encourage and endorse services in joining common frameworks.

UV-C light-activated gallic acid and ultrasound: A novel approach for reducing enteropathogens inoculated in lettuce (Lactuca sativa L.) - C.J. Alvarez-Rodríguez; N.X. Morales-Martínez; S.C. Beristain-Bauza; P. Hernández-Carranza; I.I. Ruiz-López; C.E. Ochoa-Velasco (Food Control, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

From raw microalgae to bioplastics: Conversion of Chlorella vulgaris starch granules into thermoplastic starch - A. Six; D. Dauvillée; C. Lancelon-Pin; A. Dimitriades-Lemaire; A. Compadre; C. Dubreuil; P. Alvarez; J.-F. Sassi; Y. Li-Beisson; J.-L. Putaux; N. Le Moigne; G. Fleury (Carbohydrate Polymers, 2024)

Wave-driven current and vortex patterns at an open beach: Insights from phase-resolving numerical computations and Lagrangian measurements - Andreas Bondehagen; Volker Roeber; Henrik Kalisch; Marc P. Buckley; Michael Streßer; Marius Cysewski; Jochen Horstmann; Maria Bjørnestad; Olufemi E. Ige; Hege G. Frøysa; Ruben Carrasco-Alvarez (Coastal Engineering, 2024)

Repeated migration, interbreeding and bottlenecking shaped the phylogeography of the selfing grass Brachypodium stacei - Miguel Campos; Ernesto Pérez‐Collazos; Antonio Díaz‐Pérez; Diana López‐Alvarez; Ali Oumouloud; Luis A. J. Mur; John P. Vogel; Pilar Catalán (Molecular Ecology, 2024)
Brachypodium stacei is the most ancestral lineage in the genus Brachypodium , a model system for grass functional genomics. B. stacei shows striking and sometimes contradictory biological and evolutionary features, including a high selfing rate yet extensive admixture, an ancient Miocene origin yet with recent evolutionary radiation, and adaptation to different dry climate conditions in its narrow distribution range. Therefore, it constitutes an ideal system to study these life history traits. We studied the phylogeography of 17 native circum‐Mediterranean B. stacei populations (39 individuals) using genome‐wide RADseq SNP data and complete plastome sequences. Nuclear SNP data revealed the existence of six distinct genetic clusters, low levels of intra‐population genetic diversity and high selfing rates, albeit with signatures of admixture. Coalescence‐based dating analysis detected a recent split between crown lineages in the Late Quaternary. Plastome sequences showed incongruent evolutionary relationships with those recovered by the nuclear data, suggesting interbreeding and chloroplast capture events between genetically distant populations. Demographic and population dispersal coalescent models identified an ancestral origin of B. stacei in the western‐central Mediterranean islands, followed by an early colonization of the Canary Islands and two independent colonization events of the eastern Mediterranean region through long‐distance dispersal and bottleneck events as the most likely evolutionary history. Climate niche data identified three arid niches of B. stacei in the southern Mediterranean region. Our findings indicate that the phylogeography of B. stacei populations was shaped by recent radiations, frequent extinctions, long‐distance dispersal events, occasional interbreeding, and adaptation to local climates.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

P06-10 NGS-based discovery of circulating microRNA biomarkers of drug-induced pancreatic injury (DIPI) - P. Szatmary; A. Evans; A. Jones; D. Latawiec; W. Cai; A. Kattakayam; C. Goldring; G. Beyer; S. Sirtl; I. Alvarez-Alvarez; W. Bailey; B. Ackermann; et al. (Toxicology Letters, 2024)

Performance of global retention models in the optimisation of the liquid chromatographic separation (II): Complex multi-analyte samples - P. Peiró-Vila; J.R. Torres-Lapasió; M.C. García-Alvarez-Coque (Analytica Chimica Acta, 2024)

Red light induces starch accumulation in Chlorella vulgaris without affecting photosynthesis efficiency, unlike abiotic stress - A. Six; A. Dimitriades-Lemaire; C. Lancelon-Pin; J.-L. Putaux; D. Dauvillée; D. Petroutsos; P. Alvarez Diaz; J.-F. Sassi; Y. Li-Beisson; G. Fleury (Algal Research, 2024)

Temperature-controlled 3D printing of dairy structures using cold-renneted protein-fortified milk - Ricardo Uribe-Alvarez; Craig P. Murphy; Caroline Coleman-Vaughan; Norah O'Shea (Journal of Food Engineering, 2024)

Airmass history, night-time particulate organonitrates, and meteorology impact urban SOA formation rate - Fangzhou Guo; Alexander A.T. Bui; Benjamin C. Schulze; Qili Dai; Subin Yoon; Sujan Shrestha; Henry W. Wallace; Nancy P. Sanchez; Sergio Alvarez; Matthew H. Erickson; Rebecca J. Sheesley; Sascha Usenko; et al. (Atmospheric Environment, 2024)

Diadenosine pentaphosphate regulates dendrite growth and number in cultured hippocampal neurons - M. Diez-Zaera; A. Ruiz-Calvo; J. I. Diaz-Hernandez; A. Sebastián-Serrano; P. Aivar; B. Alvarez-Castelao; J. Pintor; M. Diaz-Hernandez; M. T. Miras-Portugal (Purinergic Signalling, 2024)
During the establishment of neuronal circuits, axons and dendrites grow and branch to establish specific synaptic connections. This complex process is highly regulated by positive and negative extracellular cues guiding the axons and dendrites. Our group was pioneer in describing that one of these signals are the extracellular purines. We found that extracellular ATP, through its selective ionotropic P2X7 receptor (P2X7R), negatively regulates axonal growth and branching. Here, we evaluate if other purinergic compounds, such as the diadenosine pentaphosphate (Ap 5 A), may module the dynamics of dendritic or axonal growth and branching in cultured hippocampal neurons. Our results show that Ap 5 A negatively modulates the dendrite’s growth and number by inducing transient intracellular calcium increases in the dendrites’ growth cone. Interestingly, phenol red, commonly used as a pH indicator in culture media, also blocks the P2X1 receptors, avoided the negative modulation of Ap 5 A on dendrites. Subsequent pharmacological studies using a battery of selective P2X1R antagonists confirmed the involvement of this subunit. In agreement with pharmacological studies, P2X1R overexpression caused a similar reduction in dendritic length and number as that induced by Ap 5 A. This effect was reverted when neurons were co-transfected with the vector expressing the interference RNA for P2X1R. Despite small hairpin RNAs reverting the reduction in the number of dendrites caused by Ap 5 A, it did not avoid the dendritic length decrease induced by the polyphosphate, suggesting, therefore, the involvement of a heteromeric P2X receptor. Our results are indicating that Ap 5 A exerts a negative influence on dendritic growth.

Surface hydrophobicity of boron nitride promotes PFOA photocatalytic degradation - Bo Wang; Yu Chen; Joshua Samba; Kimberly Heck; Xiaochuan Huang; Junseok Lee; Jordin Metz; Manav Bhati; John Fortner; Qilin Li; Paul Westerhoff; Pedro Alvarez; et al. (Chemical Engineering Journal, 2024)

Occurrence and anthropogenic‐derived mortality of humpback whales ( Megaptera novaeangliae ) along the northern coast of Argentina, 2003–2021 - Gisela V. Giardino; Joaquín C. M. Gana; M. Carolina De León; M. Agustina Mandiola; Mariela Dassis; Pablo Denuncio; Andrea Elissamburu; Sergio Morón; Sergio Rodríguez Heredia; C. Karina Alvarez; Juan P. Loureiro; Victoria Massola; et al. (New Zealand Journal of Marine and Freshwater Research, 2024)
Sightings and strandings of humpback whales ( Megaptera novaeangliae ) along the coast of Buenos Aires Province in Argentina were once sporadic but have increased by up to 640% since 2018. Here, we assess the trends and seasonality of occurrence and anthropogenic‐derived mortality in this population between 2003 and 2021. Most of the humpback whales found dead were young animals, and 27% of the stranded whales showed signs of anthropogenic interactions. The information collected from Buenos Aires Province over the past two decades clearly indicates that humpback whales are becoming more frequent and growing in numbers along the Argentinean coast. For their protection, governmental regulations need to be implemented as soon as possible.

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Zinc supplementation alters tissue distribution of arsenic in Mus musculus - Erica J. Dashner-Titus; Jodi R. Schilz; Sandra A. Alvarez; Carmen P. Wong; Karen Simmons; Emily Ho; Laurie G. Hudson (Toxicology and Applied Pharmacology, 2023)

Evaluation of legumes for fermentability and protein fractions using in vitro rumen fermentation - Bereket Zeleke Tunkala; Kristy DiGiacomo; Pablo S. Alvarez Hess; Christopher P. Gardiner; Hafiz Suleria; Brian J. Leury; Frank R. Dunshea (Animal Feed Science and Technology, 2023)

Achieving coherence between the Marine Strategy Framework Directive and the Maritime Spatial Planning Directive - Th. Paramana; M. Dassenakis; N. Bassan; C. Dallangelo; P. Campostrini; S. Raicevich; F. Ronchi; G. Giorgi; A. Murillas-Maza; M.C. Uyarra; N. Papadopoulou; C. Smith; et al. (Marine Policy, 2023)

Evaluation of ionic calcium and protein concentration on heat- and cold-induced gelation of whey protein isolate gels as a potential food formulation for 3D food printing - Ricardo Uribe-Alvarez; Craig P. Murphy; Caroline Coleman-Vaughan; Norah O'Shea (Food Hydrocolloids, 2023)

Population structure and reproductive states of the dogwhelk Nucella lapillus differ between artificial structures and natural rocky shores - Bryan Thompson; Paul R. Brooks; Veronica Farrugia Drakard; Fiona Kubin; Hannah S. Earp; Ignacio Alvarez-Cienfuegos; Pippa J. Moore; Tasman P. Crowe (Marine Environmental Research, 2023)

Hair mercury is associated with dyslipidemia and cardiovascular risk: An anthropometric, biochemical and genetic cross-sectional study of Amazonian vulnerable populations. - Amanda Lopes-Araújo; Gabriela P. Arrifano; Barbarella M. Macchi; Marcus Augusto-Oliveira; Letícia Santos-Sacramento; Rosa C. Rodríguez Martín-Doimeadios; María Jiménez-Moreno; Arnaldo J. Martins Filho; Jacqueline I. Alvarez-Leite; Reinaldo B. Oriá; José Luiz M. do Nascimento; Maria Elena Crespo-Lopez (Environmental Research, 2023)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Handleable TiO2-coated zeolitic material for photodecomposition of caffeine boosted by urine matrix - Edith A. Alvarez-Aguiñaga; María P. Elizalde-González; Esmeralda García-Díaz (Environmental Science and Pollution Research, 2023)

Analysis of the cytotoxic and genotoxic effects in a population chronically exposed to coal mining residues - Grethel León-Mejía; Robinson Alvarez Rueda; Jose Pérez Pérez; Alvaro Miranda-Guevara; Ornella Fiorillo Moreno; Milton Quintana-Sosa; Cristiano Trindade; Yurina Sh De Moya; Martha Ruiz-Benitez; Yesit Bello Lemus; Ibeth Luna Rodríguez; Ludis Oliveros-Ortiz; et al. (Environmental Science and Pollution Research, 2023)
During coal mining activities, many compounds are released into the environment that can negatively impact human health. Particulate matter, polycyclic aromatic hydrocarbons (PAHs), metals, and oxides are part of the complex mixture that can affect nearby populations. Therefore, we designed this study to evaluate the potential cytotoxic and genotoxic effects in individuals chronically exposed to coal residues from peripheral blood lymphocytes and buccal cells. We recruited 150 individuals who lived more than 20 years in La Loma-Colombia and 120 control individuals from the city of Barranquilla without a history of exposure to coal mining. In the cytokinesis-block micronucleus cytome (CBMN-Cyt) assay, significant differences in the frequency of micronucleus (MN), nucleoplasmic bridge (NPB), nuclear bud (NBUD), and apoptotic cells (APOP) were observed between the two groups. In the buccal micronucleus cytome (BM-Cyt) assay, a significant formation of NBUD, karyorrhexis (KRX), karyolysis (KRL), condensed chromatin (CC), and binucleated (BN) cells was observed in the exposed group. Considering the characteristics of the study group, a significant correlation for CBMN-Cyt was found between NBUD and vitamin consumption, between MN or APOP and meat consumption, and between MN and age. Moreover, a significant correlation for BM-Cyt was found between KRL and vitamin consumption or age, and BN versus alcohol consumption. Using Raman spectroscopy, a significant increase in the concentration of DNA/RNA bases, creatinine, polysaccharides, and fatty acids was detected in the urine of individuals exposed to coal mining compared to the control group. These results contribute to the discussion on the effects of coal mining on nearby populations and the development of diseases due to chronic exposure to these residues.

Basin formation, magmatism, and exhumation document southward migrating flat-slab subduction in the central Andes - Joel E. Saylor; Kurt E. Sundell; Nicholas D. Perez; Jeffrey B. Hensley; Payton McCain; Brook Runyon; Paola Alvarez; José Cárdenas; Whitney P. Usnayo; Carlos S. Valer (Earth and Planetary Science Letters, 2023)

Evidence of SARS-CoV-2 infection in postmortem lung, kidney, and liver samples, revealing cellular targets involved in COVID-19 pathogenesis - Viviana Falcón-Cama; Teresita Montero-González; Emilio F. Acosta-Medina; Gerardo Guillen-Nieto; Jorge Berlanga-Acosta; Celia Fernández-Ortega; Anabel Alfonso-Falcón; Nathalie Gilva-Rodríguez; Lilianne López-Nocedo; Daina Cremata-García; Mariuska Matos-Terrero; Giselle Pentón-Rol; et al. (Archives of Virology, 2023)
There is an urgent need to understand severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-host interactions involved in virus spread and pathogenesis, which might contribute to the identification of new therapeutic targets. In this study, we investigated the presence of SARS-CoV-2 in postmortem lung, kidney, and liver samples of patients who died with coronavirus disease (COVID-19) and its relationship with host factors involved in virus spread and pathogenesis, using microscopy-based methods. The cases analyzed showed advanced stages of diffuse acute alveolar damage and fibrosis. We identified the SARS-CoV-2 nucleocapsid (NC) in a variety of cells, colocalizing with mitochondrial proteins, lipid droplets (LDs), and key host proteins that have been implicated in inflammation, tissue repair, and the SARS-CoV-2 life cycle (vimentin, NLRP3, fibronectin, LC3B, DDX3X, and PPARγ), pointing to vimentin and LDs as platforms involved not only in the viral life cycle but also in inflammation and pathogenesis. SARS-CoV-2 isolated from a patient´s nasal swab was grown in cell culture and used to infect hamsters. Target cells identified in human tissue samples included lung epithelial and endothelial cells; lipogenic fibroblast-like cells (FLCs) showing features of lipofibroblasts such as activated PPARγ signaling and LDs; lung FLCs expressing fibronectin and vimentin and macrophages, both with evidence of NLRP3- and IL1β-induced responses; regulatory cells expressing immune-checkpoint proteins involved in lung repair responses and contributing to inflammatory responses in the lung; CD34 + liver endothelial cells and hepatocytes expressing vimentin; renal interstitial cells; and the juxtaglomerular apparatus. This suggests that SARS-CoV-2 may directly interfere with critical lung, renal, and liver functions involved in COVID-19-pathogenesis.

The production of activated biochar using Calophyllum inophyllum waste biomass and use as an adsorbent for removal of diuron from the water in batch and fixed bed column - Dison S. P. Franco; Jordana Georgin; Claudete Gindri Ramos; Matias S. Netto; Natalia Jimenez Ojeda; Natalia Alvarez Vega; Lucas Meili; Eder C. Lima; Mu. Naushad (Environmental Science and Pollution Research, 2023)

Microplastics contamination in the fishes of selected sites in Pasig River and Marikina River in the Philippines - Emilyn Q. Espiritu; Raymond S. Rodolfo; Sofia Maria J. Evangelista; Jillian Jay G. Feliciano; Alexandra Marie N. Sumaway; Jiena Lynne R. Pauco; Karl Vincent N. Alvarez; Erwin P. Enriquez (Marine Pollution Bulletin, 2023)

Protecting environmental flows to achieve long-term water security - C. Alvarez-Garreton; J.P. Boisier; M. Billi; I. Lefort; R. Marinao; P. Barría (Journal of Environmental Management, 2023)

Relationships between land-use intensity, woody species diversity, and carbon storage in an arid woodland ecosystem - Andrea L. Magnano; Pablo A. Meglioli; Eugenia Vazquez Novoa; Verónica Chillo; Juan A. Alvarez; Leandro M. Alvarez; Carmen E. Sartor; Diego P. Vázquez; Cecilia C. Vega Riveros; Pablo E. Villagra (Forest Ecology and Management, 2023)

Cys mutants as tools to study the oligomerization of the pore-forming toxin sticholysin I - Yadira P. Hervis; Aisel Valle; Liem Canet; Azalia Rodríguez; Maria E. Lanio; Carlos Alvarez; Heinz J. Steinhoff; Isabel F. Pazos (Toxicon, 2023)

Hiking and livestock favor non-native plants in the high Andes - María Alisa Alvarez; Ana Agustina Barros; Diego P. Vázquez; Lorena de Jesús Bonjour; Jonas J. Lembrechts; Ronja E. M. Wedegärtner; Valeria Aschero (Biological Invasions, 2022)

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Physicochemical Control of Caribbean Coral Calcification Linked to Host and Symbiont Responses to Varying pCO2 and Temperature - Robert A. Eagle; Maxence Guillermic; Illian De Corte; Blanca Alvarez Caraveo; Colleen B. Bove; Sambuddha Misra; Louise P. Cameron; Karl D. Castillo; Justin B. Ries (Journal of Marine Science and Engineering, 2022)
It is thought that the active physiological regulation of the chemistry of a parent fluid is an important process in the biomineralization of scleractinian corals. Biological regulation of calcification fluid pH (pHCF) and other carbonate chemistry parameters ([CO32−]CF, DICCF, and ΩCF) may be challenged by CO2 driven acidification and temperature. Here, we examine the combined influence of changing temperature and CO2 on calcifying fluid regulation in four common Caribbean coral species—Porites astreoides, Pseudodiploria strigosa, Undaria tenuifolia, and Siderastrea siderea. We utilize skeletal boron geochemistry (B/Ca and δ11B) to probe the pHCF, [CO32−]CF, and DICCF regulation in these corals, and δ13C to track changes in the sources of carbon for calcification. Temperature was found to not influence pHCF regulation across all pCO2 treatments in these corals, in contrast to recent studies on Indo-Pacific pocilloporid corals. We find that [DIC]CF is significantly lower at higher temperatures in all the corals, and that the higher temperature was associated with depletion of host energy reserves, suggesting [DIC]CF reductions may result from reduced input of respired CO2 to the DIC pool for calcification. In addition, δ13C data suggest that under high temperature and CO2 conditions, algal symbiont photosynthesis continues to influence the calcification pool and is associated with low [DIC]CF in P. strigosa and P. astreoides. In P. astreoides this effect is also associated with an increase in chlorophyll a concentration in coral tissues at higher temperatures. These observations collectively support the assertion that physicochemical control over coral calcifying fluid chemistry is coupled to host and symbiont physiological responses to environmental change, and reveals interspecific differences in the extent and nature of this coupling.

Oxidative stress and alterations in the expression of genes related to inflammation, DNA damage, and metal exposure in lung cells exposed to a hydroethanolic coal dust extract - I. P. Tirado-Ballestas; N. Alvarez-Ortega; W. Maldonado-Rojas; J. Olivero-Verbel; K. Caballero-Gallardo (Molecular Biology Reports, 2022)

The ghost vampire: spatio-temporal distribution and conservation status of the largest bat in the Americas - F. Alvarez; S. Gomes da Silva; L. M. Guevara-Chumacero; F. Fernandes Ferreira; L. Alvarez Borla; R. Firmino de Sousa; D. P. Silva (Biodiversity and Conservation, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Comparative Assessment of GI and GA Coated AHSS LME Sensitivity During Spot Welding - D. Zapico Alvarez; Y. Benlatreche; M. Brossard; J. Giroux; C. Kaczynski; J.-M. Mataigne; C. Musik; P. Gerkens (BHM Berg- und Hüttenmännische Monatshefte, 2021)

Solvent-Assisted Hot Melt Extrusion of a Thermally Labile, High Melting Point Compound - C. Lagan; J. E. Huckle; J. M. Katz; B. Khorsand; D. Daurio; G. P. Andrews; J. Chung; F. Alvarez-Nunez (AAPS PharmSciTech, 2021)

Oral methylmercury intoxication aggravates cardiovascular risk factors and accelerates atherosclerosis lesion development in ApoE knockout and C57BL/6 mice - Janayne L. Silva; Paola C. L. Leocádio; Jonas M. Reis; Gianne P. Campos; Luciano S. A. Capettini; Giselle Foureaux; Anderson J. Ferreira; Cláudia C. Windmöller; Flávia A. Santos; Reinaldo B. Oriá; Maria E. Crespo-López; Jacqueline I. Alvarez-Leite (Toxicological Research, 2021)

Insights into the evolutionary history of the virulent factor HBHA of Mycobacterium tuberculosis - Mariana P. Lanfranconi; Ana Arabolaza; Hugo Gramajo; Héctor M. Alvarez (Archives of Microbiology, 2021)

Workflow for the Generation of Expert-Derived Training and Validation Data: A View to Global Scale Habitat Mapping - Chris M. Roelfsema; Mitchell Lyons; Nicholas Murray; Eva M. Kovacs; Emma Kennedy; Kathryn Markey; Rodney Borrego-Acevedo; Alexandra Ordoñez Alvarez; Chantel Say; Paul Tudman; Meredith Roe; Jeremy Wolff; et al. (Frontiers in Marine Science, 2021)
Our ability to completely and repeatedly map natural environments at a global scale have increased significantly over the past decade. These advances are from delivery of a range of on-line global satellite image archives and global-scale processing capabilities, along with improved spatial and temporal resolution satellite imagery. The ability to accurately train and validate these global scale-mapping programs from what we will call “reference data sets” is challenging due to a lack of coordinated financial and personnel resourcing, and standardized methods to collate reference datasets at global spatial extents. Here, we present an expert-driven approach for generating training and validation data on a global scale, with the view to mapping the world’s coral reefs. Global reefs were first stratified into approximate biogeographic regions, then per region reference data sets were compiled that include existing point data or maps at various levels of accuracy. These reference data sets were compiled from new field surveys, literature review of published surveys, and from individually sourced contributions from the coral reef monitoring and management agencies. Reference data were overlaid on high spatial resolution satellite image mosaics (3.7 m × 3.7 m pixels; Planet Dove) for each region. Additionally, thirty to forty satellite image tiles; 20 km × 20 km) were selected for which reference data and/or expert knowledge was available and which covered a representative range of habitats. The satellite image tiles were segmented into interpretable groups of pixels which were manually labeled with a mapping category via expert interpretation. The labeled segments were used to generate points to train the mapping models, and to validate or assess accuracy. The workflow for desktop reference data creation that we present expands and up-scales traditional approaches of expert-driven interpretation for both manual habitat mapping and map training/validation. We apply the reference data creation methods in the context of global coral reef mapping, though our approach is broadly applicable to any environment. Transparent processes for training and validation are critical for usability as big data provide more opportunities for managers and scientists to use global mapping products for science and conservation of vulnerable and rapidly changing ecosystems.

Drivers of N2O Emissions from Natural Forests and Grasslands Differ in Space and Time - P. I. Araujo; J. M. Piñeiro-Guerra; L. Yahdjian; M. M. Acreche; C. Alvarez; C. R. Alvarez; A. Costantini; J. Chalco Vera; J. De Tellería; T. Della Chiesa; N. A. Lewczuk; M. Petrasek; et al. (Ecosystems, 2021)

Influence of the Seasonal Thermocline on the Vertical Distribution of Larval Fish Assemblages Associated with Atlantic Bluefin Tuna Spawning Grounds - Itziar Alvarez; Leif K. Rasmuson; Trika Gerard; Raul Laiz-Carrion; Manuel Hidalgo; John T. Lamkin; Estrella Malca; Carmen Ferra; Asvin P. Torres; Diego Alvarez-Berastegui; Francisco Alemany; Jose M. Quintanilla; et al. (Oceans, 2021)
Temperature is often an important variable influencing the vertical position of fish larvae in the water column. The same species may show different vertical distributions in areas with a strong near-surface seasonal thermocline compared to isothermal near-surface regions. In areas with a strong surface thermocline, tuna larvae show a significant preference for the near-surface warmer layers. Little is known regarding larval tuna vertical distribution in isothermal waters and on the vertical distribution of the associated larval fish assemblages. We conducted vertical stratified sampling using the same methodology and fishing device (MOCNESS) in the two major spawning areas of Atlantic bluefin tuna (BFT): western Mediterranean Sea (MED), characterized by a surface thermocline, and the Gulf of Mexico (GOM) which lacks thermal stratification. Tuna larvae occupied the upper 30 m in both areas, but the average larval depth distribution was consistently deeper in the GOM. In the MED, vertical distribution of larval fish assemblages was explained by temperature, and species such as BFT, Thunnus alalunga, and Ceratoscopelus maderensis, among others, coexist above the thermocline and are separated from species such as Cyclothone braueri and Hygophum spp. (found below the thermocline). In the GOM, the environmental correlates of the vertical distribution of the larvae were salinity and fluorescence. Mesopelagic taxa such as Ceratoscopelus spp. and Cyclothone spp., among others, had a shallower average distribution than Lampanyctus spp., Hygophum spp., and Myctophum spp.

COVID-19: the impact of a global crisis on sustainable development research - Walter Leal Filho; Anabela Marisa Azul; Tony Wall; Claudio R. P. Vasconcelos; Amanda Lange Salvia; Arminda do Paço; Kalterina Shulla; Vanessa Levesque; Federica Doni; Lorena Alvarez-Castañón; Claudia Mac-lean; Lucas Veiga Avila; et al. (Sustainability Science, 2021)

Correction to: Energy Benchmarking as a Tool for Energy-Efficient Wastewater Treatment: Reviewing International Applications - Ilda Clos; Jörg Krampe; Juan P. Alvarez-Gaitan; Christopher P. Saint; Michael D. Short (Water Conservation Science and Engineering, 2020)

Observed trends in daily temperature extreme indices in Aguascalientes, Mexico - Osias Ruiz-Alvarez; Vijay P. Singh; Juan Enciso-Medina; Ronald Ernesto Ontiveros-Capurata; Carlos Antonio Costa dos Santos (Theoretical and Applied Climatology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Nanoparticulated Systems Based on Natural Polymers Loaded with Miconazole Nitrate and Lidocaine for the Treatment of Topical Candidiasis - G. Tejada; M. G. Barrera; P. García; M. Sortino; M. C. Lamas; V. Lassalle; V. Alvarez; D. Leonardi (AAPS PharmSciTech, 2020)

A New Approach to Ex Vivo Permeation Studies in In-Situ Film-Forming Systems - Amanda F. Silva-Alvarez; Maíra P. Ferreira; Fabiana T. M. C. Vicentini; Vinicius Pedrazzi; Osvaldo de Freitas (AAPS PharmSciTech, 2020)

Micropropagation protocol for coastal quinoa - J. J. Regalado; V. E. Tossi; H. P. Burrieza; C. L. Encina; S. I. Pitta-Alvarez (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

A first-of-its-kind multi-model convection permitting ensemble for investigating convective phenomena over Europe and the Mediterranean - Erika Coppola; Stefan Sobolowski; E. Pichelli; F. Raffaele; B. Ahrens; I. Anders; N. Ban; S. Bastin; M. Belda; D. Belusic; A. Caldas-Alvarez; R. M. Cardoso; et al. (Climate Dynamics, 2020)

Energy Benchmarking as a Tool for Energy-Efficient Wastewater Treatment: Reviewing International Applications - Ilda Clos; Jörg Krampe; Juan P. Alvarez-Gaitan; Christopher P. Saint; Michael D. Short (Water Conservation Science and Engineering, 2020)

Unexpected but unsurprising lineage diversity within the most widespread Neotropical crocodilian genus Caiman (Crocodylia, Alligatoridae) - Igor J. Roberto; Pedro S. Bittencourt; Fabio L. Muniz; Sandra M. Hernández-Rangel; Yhuri C. Nóbrega; Robson W. Ávila; Bruno C. Souza; Gustavo Alvarez; Guido Miranda-Chumacero; Zilca Campos; Izeni P. Farias; Tomas Hrbek (Systematics and Biodiversity, 2020)

Creation and characterization of an immortalized canine myoblast cell line: Myok9 - Sara Mata López; Cynthia Balog-Alvarez; Emily H. Canessa; Yetrib Hathout; Kristy J. Brown; Stanislav Vitha; Amanda K. Bettis; Jessica Boehler; Joe N. Kornegay; Peter P. Nghiem (Mammalian Genome, 2020)

Antarctic phytoplankton community composition and size structure: importance of ice type and temperature as regulatory factors - T. E. G. Biggs; S. Alvarez-Fernandez; C. Evans; K. D. A. Mojica; P. D. Rozema; H. J. Venables; D. W. Pond; C. P. D. Brussaard (Polar Biology, 2019)

The discovery of Neotropical Lepidosira (Collembola, Entomobryidae) and its systematic position - Rudy C. Nunes; Nerivânia N. Godeiro; George Pacheco; Shanlin Liu; Marcus Thomas P. Gilbert; Fernando Alvarez‐Valin; Feng Zhang; Bruno C. Bellini (Zoologica Scripta, 2019)
We herein present the first reliable record of Lepidosira from Neotropical Region. Lepidosira neotropicalis sp. n. from Brazil is described and illustrated in detail, including its complete mitochondrial genome. We perform a Bayesian phylogenetic analysis to place the new species within the Entomobryidae, and at the same time to test previous contrasting hypotheses on Lepidosira position within the Entomobryinae versus Seirinae for the first time. Phylogenetic analyses were based on one mitochondrial and two nuclear genes, Cytochrome Oxidase subunit I, 18S ribosomal RNA and 28S ribosomal RNA, respectively. Lepidosira neotropicalis sp. n. resembles L. sundana Yoshii and Suhardjono and L. nigropunctata (Nguyen) in dorsal chaetotaxy of abdominal segments I and II, but differs from all other species by the combination of head (dorsally and ventrally) and dorsal trunk chaetotaxy, plus empodial complex morphology. Our phylogenetic analyses support the placement of Lepidosira within Entomobryinae, as the sister group of Lepidocyrtoides . Overall, our revision enables a more objective diagnosis to Lepidosira and suggests that the genus is in need of a full revision due to its variable morphology, and lack of data needed to evaluate its monophyly. Finally, we provide an identification key for Neotropical genera of Entomobryinae.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Zinc Deficiency and Arsenic Exposure Can Act Both Independently or Cooperatively to Affect Zinc Status, Oxidative Stress, and Inflammatory Response - Carmen P. Wong; Erica J. Dashner-Titus; Sandra C. Alvarez; Tyler T. Chase; Laurie G. Hudson; Emily Ho (Biological Trace Element Research, 2019)

Role of Antarctic yeast in biocontrol of Penicillium expansum and patulin reduction of apples - Angie Alvarez; Romina Gelezoglo; Gabriela Garmendia; María L. González; Alejandra P. Magnoli; Eloisa Arrarte; Lilia R. Cavaglieri; Silvana Vero (Environmental Sustainability, 2019)

Optical properties of atmospheric particles over an urban site in Mexico City and a peri-urban site in Queretaro - Rafael N. Liñán-Abanto; O. Peralta; D. Salcedo; L. G. Ruiz-Suárez; P. Arnott; G. Paredes-Miranda; H. Alvarez-Ospina; T. Castro (Journal of Atmospheric Chemistry, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Microbial Diversity Exploration of Marine Hosts at Serrana Bank, a Coral Atoll of the Seaflower Biosphere Reserve - Astrid Catalina Alvarez-Yela; Jeanneth Mosquera-Rendón; Alejandra Noreña-P; Marco Cristancho; Diana López-Alvarez (Frontiers in Marine Science, 2019)

Groundwater Recharge Assessment in an Arid, Coastal, Middle Mountain Copper Mining District, Coquimbo Region, North-central Chile - Jorge Oyarzún; Jorge Núñez; Jerry P. Fairley; Sebastián Tapia; Diana Alvarez; Hugo Maturana; José Luis Arumí; Evelyn Aguirre; Alfonso Carvajal; Ricardo Oyarzún (Mine Water and the Environment, 2019)

Correction to: Spatio-temporal trends in monthly pan evaporation in Aguascalientes, Mexico - Osias Ruiz-Alvarez; Vijay P. Singh; Juan Enciso-Medina; Clyde Munster; Ronald Kaiser; Ronald Ernesto Ontiveros-Capurata; Luis Antonio Diaz-Garcia; Carlos Antonio Costa dos Santos (Theoretical and Applied Climatology, 2019)

Spatio-temporal trends in monthly pan evaporation in Aguascalientes, Mexico - Osias Ruiz-Alvarez; Vijay P. Singh; Juan Enciso-Medina; Clyde Munster; Ronald Kaiser; Ronald Ernesto Ontiveros-Capurata; Luis Antonio Diaz-Garcia; Carlos Antonio Costa dos Santos (Theoretical and Applied Climatology, 2019)

Analyzing the Impacts of Elevated-CO2 Levels on the Development of a Subtropical Zooplankton Community During Oligotrophic Conditions and Simulated Upwelling - María Algueró-Muñiz; Henriette G. Horn; Santiago Alvarez-Fernandez; Carsten Spisla; Nicole Aberle; Lennart T. Bach; Wanchun Guan; Eric P. Achterberg; Ulf Riebesell; Maarten Boersma (Frontiers in Marine Science, 2019)

Microbial Communities of the Gut and Nest of the Humus- and Litter-Feeding Termite Procornitermes araujoi (Syntermitinae) - Edimar A. Moreira; Thabata M. Alvarez; Gabriela F. Persinoti; Douglas Antonio Alvaredo Paixão; Letícia R. Menezes; João P. Franco Cairo; Fabio Marcio Squina; Ana M. Costa-Leonardo; Tiago Carrijo; Alberto Arab (Current Microbiology, 2018)

Determinants of ant species spatial distribution in habitats from central Argentina - J. Tavella; A. P. Alvarez Pringles; L. Cagnolo (Community Ecology, 2018)

A novel method to estimate the spatial scale of mate choice in the wild - Daniel Estévez; Terence P. T. Ng; Mónica Fernández-Meirama; Jorien M. Voois; Antonio Carvajal-Rodríguez; Gray A. Williams; Juan Galindo; Emilio Rolán-Alvarez (Behavioral Ecology and Sociobiology, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Rhodococcus bacteria as a promising source of oils from olive mill wastes - O. Marisa Herrero; María S. Villalba; Mariana P. Lanfranconi; Héctor M. Alvarez (World Journal of Microbiology and Biotechnology, 2018)

Diaporthe from walnut tree (Juglans regia) in China, with insight of the Diaporthe eres complex - XinLei Fan; Qin Yang; Jadson D. P. Bezerra; Lourdes V. Alvarez; ChengMing Tian (Mycological Progress, 2018)

Multi-faceted Characterization of Wet-milled Griseofulvin Nanosuspensions for Elucidation of Aggregation State and Stabilization Mechanisms - M. Li; P. Alvarez; P. Orbe; E. Bilgili (AAPS PharmSciTech, 2018)

Detection of honey bee viruses in Argentinian stingless bees (Hymenoptera: Apidae) - L J Alvarez; F J Reynaldi; P J Ramello; M L G Garcia; G H Sguazza; A H. Abrahamovich; M Lucia (Insectes Sociaux, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Antimicrobial activity of octenidine against multidrug-resistant Gram-negative pathogens - R. Alvarez-Marin; M. Aires-de-Sousa; P. Nordmann; N. Kieffer; L. Poirel (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Biophysical and biochemical strategies to understand membrane binding and pore formation by sticholysins, pore-forming proteins from a sea anemone - Carlos Alvarez; Uris Ros; Aisel Valle; Lohans Pedrera; Carmen Soto; Yadira P. Hervis; Sheila Cabezas; Pedro A. Valiente; Fabiola Pazos; Maria E. Lanio (Biophysical Reviews, 2017)

Explaining the performance of irrigation communities in a water-scarce region - F. Alcon; P. A. García-Bastida; M. Soto-García; V. Martínez-Alvarez; B. Martin-Gorriz; A. Baille (Irrigation Science, 2017)

Whole genome sequencing reveals a 7 base-pair deletion in DMD exon 42 in a dog with muscular dystrophy - Peter P. Nghiem; Luca Bello; Cindy Balog-Alvarez; Sara Mata López; Amanda Bettis; Heather Barnett; Briana Hernandez; Scott J. Schatzberg; Richard J. Piercy; Joe N. Kornegay (Mammalian Genome, 2017)

Sources of trace metals in PM10 from a petrochemical industrial complex in Northern Mexico - P. F. Rodriguez-Espinosa; R. M. Flores-Rangel; V. Mugica-Alvarez; S. S. Morales-Garcia (Air Quality, Atmosphere & Health, 2017)

Effectiveness of acellular pertussis vaccination during childhood (<7 years of age) for preventing pertussis in household contacts 1–9 years old in Catalonia and Navarra (Spain) - P. Plans; D. Toledo; M. R. Sala; N. Camps; M. Villanova; R. Rodríguez; J. Alvarez; R. Solano; M. García-Cenoz; I. Barrabeig; P. Godoy; S. Minguell (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Evaluating the surface circulation in the Ebro delta (northeastern Spain) with quality-controlled high-frequency radar measurements - P. Lorente; S. Piedracoba; J. Soto-Navarro; E. Alvarez-Fanjul (Ocean Science, 2015)
The Ebro River delta is a relevant marine protected area in the western Mediterranean. In order to promote the conservation of its ecosystem and support operational decision making in this sensitive area, a three-site standard-range (13.5 MHz) CODAR SeaSonde high-frequency (HF) radar was deployed in December 2013. The main goal of this work is to explore basic features of the sea surface circulation in the Ebro deltaic region as derived from reliable HF radar surface current measurements. For this aim, a combined quality control methodology was applied: firstly, 1-year long (2014) real-time web monitoring of nonvelocity-based diagnostic parameters was conducted to infer both radar site status and HF radar system performance. The signal-to-noise ratio at the monopole exhibited a consistent monthly evolution, although some abrupt decreases (below 10 dB), occasionally detected in June for one of the radar sites, impacted negatively on the spatiotemporal coverage of total current vectors. It seemed to be sporadic episodes since radar site overall performance was found to be robust during 2014. Secondly, a validation of HF radar data with independent in situ observations from a moored current meter was attempted for May–October 2014. The accuracy assessment of radial and total vectors revealed a consistently high agreement. The directional accuracy of the HF radar was rated at better than 8°. The correlation coefficient and root mean square error (RMSE) values emerged in the ranges [0.58–0.83] and [4.02–18.31] cm s−1, respectively. The analysis of the monthly averaged current maps for 2014 showed that the HF radar properly represented basic oceanographic features previously reported, namely, the predominant southwestward flow, the coastal clockwise eddy confined south of the Ebro delta mouth, or the Ebro River impulsive-type freshwater discharge. The EOF analysis related the flow response to local wind forcing and confirmed that the surface current field evolved in space and time according to three significantly dominant modes of variability.

Differential gene transcription, biochemical responses, and cytotoxicity assessment in Pacific oyster Crassostrea gigas exposed to ibuprofen - Miguel A. S. Serrano; Maria Gonzalez-Rey; Jacó J. Mattos; Fabrício Flores-Nunes; Álvaro C. P. Mello; Flávia L. Zacchi; Clei E. Piazza; Marília N. Siebert; Rômi S. Piazza; Diana Alvarez-Muñoz; Sara Rodriguez-Mozaz; Damià Barceló; et al. (Environmental Science and Pollution Research, 2015)

COST action TD1407: network on technology-critical elements (NOTICE)—from environmental processes to human health threats - A. Cobelo-García; M. Filella; P. Croot; C. Frazzoli; G. Du Laing; N. Ospina-Alvarez; S. Rauch; P. Salaun; J. Schäfer; S. Zimmermann (Environmental Science and Pollution Research, 2015)

Vertical distribution and migration of fish larvae in the NW Iberian upwelling system during the winter mixing period: implications for cross‐shelf distribution - J.M. Rodriguez; A. Cabrero; J. Gago; C. Guevara‐Fletcher; M. Herrero; A. Hernandez de Rojas; A. Garcia; R. Laiz‐Carrion; A.R. Vergara; P. Alvarez; C. Piñeiro; F. Saborido‐Rey (Fisheries Oceanography, 2015)
The vertical distribution and vertical migrations of fish larvae and implications for their cross‐shelf distribution were investigated in the northern limit of the NE Atlantic upwelling region during the late winter mixing period of 2012. The average positive values of the upwelling index for February and March of this year were far from normal, although the average hydrographic conditions during the period of study were of downwelling and the water column was completely mixed. Fish larvae, most in the preflexion stage, were concentrated in the upper layers of the water column and their distribution was depth stratified, both day and night. However, the larval fish community was not structured in the vertical plane and fish larvae did not show significant diel vertical migration ( DVM ), although five species showed ontogenetic vertical migration. In regions of coastal upwelling and in the absence of DVM , the location of fish larvae in the water column is crucial for their cross‐shelf distribution. Thus, the cross‐shelf distribution of the six most abundant species collected in this study can be explained by the surface onshore flow associated with coastal downwelling, retaining larvae of the coastal spawning species with a relatively shallow distribution in the shelf region and transporting larvae of slope spawning species onto the shelf. The wide vertical distribution shown by larvae of the offshore spawning species could be an adaptation of these species to ensure that some larvae reach the inshore nursery areas.

Tissue targeting of the European flat oyster, Ostrea edulis, using microencapsulated microbeads as a biological proxy - G. Darmody; A. P. Maloy; S. A. Lynch; M. Prado-Alvarez; J. Cotterill; T. Wontner-Smith; S. C. Culloty (Aquaculture International, 2015)

Spatial and Temporal Variation of Dung Beetle Assemblages in a Fragmented Landscape at Eastern Humid Chaco - M P Damborsky; M C Alvarez Bohle; M G Ibarra Polesel; E A Porcel; J L Fontana (Neotropical Entomology, 2015)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Antidepressant prescribing in five European countries: application of common definitions to assess the prevalence, clinical observations, and methodological implications - V. Abbing-Karahagopian; C. Huerta; P. C. Souverein; F. de Abajo; H. G. M. Leufkens; J. Slattery; Y. Alvarez; M. Miret; M. Gil; B. Oliva; U. Hesse; G. Requena; et al. (European Journal of Clinical Pharmacology, 2014)

Physical forcing and physical/biochemical variability of the Mediterranean Sea: a review of unresolved issues and directions for future research - P. Malanotte-Rizzoli; V. Artale; G. L. Borzelli-Eusebi; S. Brenner; A. Crise; M. Gacic; N. Kress; S. Marullo; M. Ribera d'Alcalà; S. Sofianos; T. Tanhua; A. Theocharis; et al. (Ocean Science, 2014)
This paper is the outcome of a workshop held in Rome in November 2011 on the occasion of the 25th anniversary of the POEM (Physical Oceanography of the Eastern Mediterranean) program. In the workshop discussions, a number of unresolved issues were identified for the physical and biogeochemical properties of the Mediterranean Sea as a whole, i.e., comprising the Western and Eastern sub-basins. Over the successive two years, the related ideas were discussed among the group of scientists who participated in the workshop and who have contributed to the writing of this paper. Three major topics were identified, each of them being the object of a section divided into a number of different sub-sections, each addressing a specific physical, chemical or biological issue: 1. Assessment of basin-wide physical/biochemical properties, of their variability and interactions. 2. Relative importance of external forcing functions (wind stress, heat/moisture fluxes, forcing through straits) vs. internal variability. 3. Shelf/deep sea interactions and exchanges of physical/biogeochemical properties and how they affect the sub-basin circulation and property distribution. Furthermore, a number of unresolved scientific/methodological issues were also identified and are reported in each sub-section after a short discussion of the present knowledge. They represent the collegial consensus of the scientists contributing to the paper. Naturally, the unresolved issues presented here constitute the choice of the authors and therefore they may not be exhaustive and/or complete. The overall goal is to stimulate a broader interdisciplinary discussion among the scientists of the Mediterranean oceanographic community, leading to enhanced collaborative efforts and exciting future discoveries.

Fast demographic traits promote high diversification rates of Amazonian trees - Timothy R. Baker; R. Toby Pennington; Susana Magallon; Emanuel Gloor; William F. Laurance; Miguel Alexiades; Esteban Alvarez; Alejandro Araujo; Eric J. M. M. Arets; Gerardo Aymard; Atila Alves de Oliveira; Iêda Amaral; et al. (Ecology Letters, 2014)
The Amazon rain forest sustains the world's highest tree diversity, but it remains unclear why some clades of trees are hyperdiverse, whereas others are not. Using dated phylogenies, estimates of current species richness and trait and demographic data from a large network of forest plots, we show that fast demographic traits – short turnover times – are associated with high diversification rates across 51 clades of canopy trees. This relationship is robust to assuming that diversification rates are either constant or decline over time, and occurs in a wide range of Neotropical tree lineages. This finding reveals the crucial role of intrinsic, ecological variation among clades for understanding the origin of the remarkable diversity of Amazonian trees and forests.

Can upwelling signals be detected in intertidal fishes of different trophic levels? - J. Pulgar; E. Poblete; M. Alvarez; J. P. Morales; B. Aranda; M. Aldana; V. M. Pulgar (Journal of Fish Biology, 2013)
For intertidal fishes belonging to three species, the herbivore Scartichthys viridis (Blenniidae), the omnivore Girella laevifrons (Kyphosidae) and the carnivore Graus nigra (Kyphosidae), mass and body size relationships were higher in individuals from an upwelling zone compared with those from a non‐upwelling zone. RNA : DNA were higher in the herbivores and omnivores from the upwelling zone. Higher biomass and RNA : DNA in the upwelling intertidal fishes may be a consequence of an increased exposure to higher nutrient availability, suggesting that increased physiological conditioning in vertebrates from upwelling areas can be detected and measured using intertidal fishes of different trophic levels.

Silvopastoral use of Nothofagus antarctica in Southern Patagonian forests, influence over net nitrogen soil mineralization - Héctor A. Bahamonde; P. L. Peri; R. Alvarez; A. Barneix; A. Moretto; G. Martínez Pastur (Agroforestry Systems, 2013)

Soil nitrous oxide emissions under different management practices in the semiarid region of the Argentinian Pampas - Carolina Alvarez; Alejandro Costantini; Carina R. Alvarez; Bruno J. R. Alves; Claudia P. Jantalia; Eduardo E. Martellotto; Segundo Urquiaga (Nutrient Cycling in Agroecosystems, 2012)

Comparison of two methods of reciprocal recurrent selection in maize (Zea mays L.) - B. Ordas; A. Butron; A. Alvarez; P. Revilla; R. A. Malvar (Theoretical and Applied Genetics, 2012)

Litter decomposition and nutrients dynamics in Nothofagus antarctica forests under silvopastoral use in Southern Patagonia - Héctor A. Bahamonde; P. L. Peri; R. Alvarez; A. Barneix; A. Moretto; G. Martínez Pastur (Agroforestry Systems, 2012)

Proteomics in evolutionary ecology: linking the genotype with the phenotype - ANGEL P. DIZ; MÓNICA MARTÍNEZ‐FERNÁNDEZ; EMILIO ROLÁN‐ALVAREZ (Molecular Ecology, 2012)
The study of the proteome (proteomics), which includes the dynamics of protein expression, regulation, interactions and its function, has played a less prominent role in evolutionary and ecological investigations in comparison with the study of the genome and transcriptome. There are, however, a number of arguments suggesting that this situation should change. First, the proteome is closer to the phenotype than the genome or the transcriptome, and as such may be more directly responsive to natural selection, and thus closely linked to adaptation. Second, there is evidence of a low correlation between protein and transcript expression levels across genes in many different organisms. Finally, there have been some recent important technological improvements in proteomics methods that make them feasible, practical and useful to address a wide range of evolutionary questions even in nonmodel organisms. The different proteomic methods, their limitations and problems when interpreting empirical data are described and discussed. In addition, the proteomic literature pertaining to evolutionary ecology is reviewed with examples, and potential applications of proteomics in a variety of evolutionary contexts are outlined. New proteomic research trends such as the study of posttranslational modifications and protein–protein interactions, as well as the combined use of the different ‐omics approaches, are discussed in relation to the development of a more functional and integrated perspective, needed for achieving a more comprehensive knowledge of evolutionary change.

Assessment of infection with polyomaviruses BKV, JCV and SV40 in different groups of Cuban individuals - Pedro A. Martínez; Vivian Kourí; Gustavo Cordero; Consuelo Correa; Yudira Soto; Virginia Capó; Licet González; Bienvenido Grá; Gregorio Petirena; César Silvério; Norma Hondal; Mabel González; et al. (Archives of Virology, 2012)

Molecular survey of concrete sewer biofilm microbial communities - Jorge W. Santo Domingo; Randy P. Revetta; Brandon Iker; Vicente Gomez-Alvarez; Jarissa Garcia; John Sullivan; James Weast (Biofouling, 2011)

Residual concentrations of the flukicidal compound triclabendazole in dairy cows’ milk and cheese - F. Imperiale; P. Ortiz; M. Cabrera; C. Farias; J.M. Sallovitz; S. Iezzi; J. Pérez; L. Alvarez; C. Lanusse (Food Additives & Contaminants: Part A, 2011)

Seasonal physiological plasticity and recovery capacity after summer stress in Mediterranean scrub communities - M. Zunzunegui; Maria Cruz Díaz Barradas; F. Ain-Lhout; L. Alvarez-Cansino; M. P. Esquivias; F. García Novo (Plant Ecology, 2011)

Influence of the KDEL signal, DMSO and mannitol on the production of the recombinant antibody 14D9 by long-term Nicotiana tabacum cell suspension culture - J. López; F. Lencina; S. Petruccelli; P. Marconi; M. A. Alvarez (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Risk factors for multidrug-resistant Pseudomonas aeruginosa acquisition. Impact of antibiotic use in a double case–control study - M. Montero; M. Sala; M. Riu; F. Belvis; M. Salvado; S. Grau; J. P. Horcajada; F. Alvarez-Lerma; R. Terradas; M. Orozco-Levi; X. Castells; H. Knobel (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Integrating the multiple dimensions of genomic and epigenomic landscapes of cancer - Raj Chari; Kelsie L. Thu; Ian M. Wilson; William W. Lockwood; Kim M. Lonergan; Bradley P. Coe; Chad A. Malloff; Adi F. Gazdar; Stephen Lam; Cathie Garnis; Calum E. MacAulay; Carlos E. Alvarez; et al. (Cancer and Metastasis Reviews, 2010)

Does the disturbance hypothesis explain the biomass increase in basin‐wide Amazon forest plot data? - M. GLOOR; O. L. PHILLIPS; J. J. LLOYD; S. L. LEWIS; Y. MALHI; T. R. BAKER; G. LÓPEZ‐GONZALEZ; J. PEACOCK; S. ALMEIDA; A. C. ALVES De OLIVEIRA; E. ALVAREZ; I. AMARAL; et al. (Global Change Biology, 2009)
Positive aboveground biomass trends have been reported from old‐growth forests across the Amazon basin and hypothesized to reflect a large‐scale response to exterior forcing. The result could, however, be an artefact due to a sampling bias induced by the nature of forest growth dynamics. Here, we characterize statistically the disturbance process in Amazon old‐growth forests as recorded in 135 forest plots of the RAINFOR network up to 2006, and other independent research programmes, and explore the consequences of sampling artefacts using a data‐based stochastic simulator. Over the observed range of annual aboveground biomass losses, standard statistical tests show that the distribution of biomass losses through mortality follow an exponential or near‐identical Weibull probability distribution and not a power law as assumed by others. The simulator was parameterized using both an exponential disturbance probability distribution as well as a mixed exponential–power law distribution to account for potential large‐scale blowdown events. In both cases, sampling biases turn out to be too small to explain the gains detected by the extended RAINFOR plot network. This result lends further support to the notion that currently observed biomass gains for intact forests across the Amazon are actually occurring over large scales at the current time, presumably as a response to climate change.

Genetic structure and evolution of Alpine polyploid complexes: Ranunculus kuepferi (Ranunculaceae) as a case study - J. BURNIER; S. BUERKI; N. ARRIGO; P. KÜPFER; N. ALVAREZ (Molecular Ecology, 2009)
The alpine white‐flowered buttercup, Ranunculus kuepferi Greuter & Burdet, is a polyploid complex with diploids endemic to the southwestern Alps and polyploids – which have been previously described as apomictic – widespread throughout European mountains. Due to the polymorphic status of both its ploidy level and its reproductive mode, R. kuepferi represents a key species for understanding the evolution of polyploid lineages in alpine habitats. To disentangle the phylogeography of this polyploid taxon, we used cpDNA sequences and AFLP (amplified fragment length polymorphism) markers in 33 populations of R. kuepferi representative of its ploidy level and distribution area. Polyploid individuals were shown to be the result of at least two polyploidization events that may have taken place in the southwestern Alps. From this region, one single main migration of tetraploids colonized the entire Alpine range, the Apennines and Corsica. Genetic recombination among tetraploids was also observed, revealing the facultative nature of the apomictic reproductive mode in R. kuepferi polyploids. Our study shows the contrasting role played by diploid lineages mostly restricted to persistent refugia and by tetraploids, whose dispersal abilities have permitted their range extension all over the previously glaciated Alpine area and throughout neighbouring mountain massifs.

Seasonal susceptibility of citrus scions to Phytophthora citrophthora and P. nicotianae and the influence of environmental and host-linked factors on infection development - L. A. Alvarez; D. Gramaje; P. Abad-Campos; J. García-Jiménez (European Journal of Plant Pathology, 2009)

Influence of Helicobacter pylori infection on the expression of MLH1 and MGMT in patients with chronic gastritis and gastric cancer - W. Bartchewsky; M. R. Martini; A. C. Squassoni; M. C. Alvarez; M. S. P. Ladeira; D. M. F. Salvatore; M. A. Trevisan; J. Pedrazzoli; M. L. Ribeiro (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Endemic linezolid-resistant Staphylococcus epidermidis in a critical care unit - M. Treviño; L. Martínez-Lamas; P. A. Romero-Jung; J. M. Giráldez; J. Alvarez-Escudero; B. J. Regueiro (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Residual effects of natural Zn chelates on navy bean response, Zn leaching and soil Zn status - J. M. Alvarez; P. Almendros; D. Gonzalez (Plant and Soil, 2009)

Comparing geographical genetic differentiation between candidate and noncandidate loci for adaptation strengthens support for parallel ecological divergence in the marine snail Littorina saxatilis - J. GALINDO; P. MORÁN; E. ROLÁN‐ALVAREZ (Molecular Ecology, 2009)
The Galician sympatric ecotypes of Littorina saxatilis have been proposed as a model system for studying parallel ecological speciation. Such a model system makes a clear prediction: candidate loci (for divergent adaptation) should present a higher level of geographical differentiation than noncandidate (neutral) loci. We used 2356 amplified fragment length polymorphisms (AFLPs) and four microsatellite loci to identify candidate loci for ecological adaptation using the F ST outlier method. Three per cent of the studied AFLP loci were identified as candidate loci associated with adaptation, after multitest adjustments, thus contributing to ecotype differentiation (candidate loci were not detected within ecotypes). Candidate and noncandidate loci were analysed separately at four different F ST partitions: differences between ecotypes (overall and local), differences between localities and micro‐geographical differences within ecotypes. The magnitude of F ST differed between candidate and noncandidate loci for all partitions except in the case of microgeographical differentiation within ecotypes, and the microsatellites (putatively neutral) showed an identical pattern to noncandidate loci. Thus, variation in candidate loci is determined partially independent by divergent natural selection (in addition to stochastic forces) at each locality, while noncandidate loci are exclusively driven by stochastic forces. These results support the evolutionary history described for these particular populations, considered to be a clear example of incomplete sympatric ecological speciation.

Microbial community response to a release of neat ethanol onto residual hydrocarbons in a pilot‐scale aquifer tank - Natalie L. Cápiro; Marcio L. B. Da Silva; Brent P. Stafford; William G. Rixey; Pedro J. J. Alvarez (Environmental Microbiology, 2008)
Summary The microbial community response to a neat ethanol release (E100, 76 l) onto residual hydrocarbons in sandy soil was evaluated in a continuous‐flow 8 m 3 pilot‐scale aquifer tank, simulating a release at a bulk fuel terminal. Microbial genotypic shifts were assessed using quantitative real‐time PCR analysis. High ethanol concentrations in the capillary fringe at potentially toxic levels, exceeding 100 000 mg l −1 , were tolerated by the microbial community. The high biochemical oxygen demand exerted by ethanol rapidly induced anaerobic conditions, and both methane production (up to 1.2 mg l −1 ) and growth of putative methanogenic Archaea (up to 10 6 gene copies per g of soil) were observed in shallow groundwater and soil samples 75 cm down gradient from the source. Aerobic conditions returned after ethanol was flushed out of the system, approximately 45 days after the spill (less than 7.5 pore volumes flushed). Total Bacteria growth coincided with ethanol migration and availability, which was restricted to a relatively thin layer at the capillary fringe and water table interface. The concentrations of bacteria harbouring the aerobic catabolic genes dmpN (coding for phenol hydroxylase) and todC1 (coding for toluene dioxygenase) increased (up to 100×) down gradient from the source, likely as a result of both fortuitous growth on ethanol and on aromatic hydrocarbons mobilized by ethanol. Growth of hydrocarbon degraders was corroborated by denaturing gradient gel electrophoresis analysis showing proliferation of Azospirillum and Brevundimonas spp., which are bacteria commonly associated with microaerophilic hydrocarbon degradation. Nevertheless, the relative abundance of hydrocarbon‐specific degraders (as a fraction of total Bacteria ) decreased as other bacteria grew to a higher extent. Overall, the observed growth of hydrocarbon degraders suggests a potential enhancement in aerobic natural attenuation in shallow aquifers after ethanol and its degradation by‐products are degraded or flushed from sites impacted by ethanol‐blended fuels.

Feasibility Analysis of the Use of Binary Genetic Algorithms as Importance Samplers Application to a 1-D DC Resistivity Inverse Problem - J. P. Fernández Alvarez; J. L. Fernández Martínez; C. O. Menéndez Pérez (Mathematical Geosciences, 2008)

Comparative Study of Blood Lead Levels in Uruguayan Children (1994–2004) - A. Cousillas; L. Pereira; C. Alvarez; T. Heller; B. De Mattos; C. Piastra; P. Viapiana; O. Rampoldi; N. Mañay (Biological Trace Element Research, 2008)

Substantial loss of genetic variation in a single generation of Senegalese sole ( Solea senegalensis ) culture: implications in the domestication process - J. Porta; J Maria Porta; P. Cañavate; G. Martínez‐Rodríguez; M Carmen Alvarez (Journal of Fish Biology, 2007)
The flatfish Solea senegalensis represents an important resource in modern mariculture and is largely raised in South Spain and Portugal. Substantial progress has been achieved in its domestication, though suitable reproduction and zootechnical conditions still remain unknown. Difficulties to obtain breeders from wild lead many companies to set up broodstocks with first generation (G1) progeny without genetic guidelines. To study the genetic processes underlying the early stage of domestication of this species, the genetic structure of four representative broodstocks from Southern Spain has been assessed by means of eight microsatellite loci . Data revealed a substantial reduction in levels of genetic variability on just one generation in stocks totally or partially composed of G1 individuals when compared with those solely integrated by individuals from wild. The genetic relatedness within the four stocks has been established, having detected close relationships between individuals from cultured origin, thus suggesting that the loss of variability is apparently due to setting up broodstocks by blind selecting of family related G1 individuals. The high proportion of siblings in these stocks can have negative consequences in future generations due to inbreeding effects. The relationships between the four broodstocks were traced, having found a common origin between two of them, which come from the same donor hatchery, thus enhancing the homogenization of the existent resources for S. senegalensis among the various stocks. This finding alerts about the risks in exchanging fish between hatcheries without knowing their genetic origin. From this study, the use of microsatellites is strongly recommended to control the genetic composition of S. senegalensis broodstocks, aimed to maintain standards of genetic health and improve their reproduction capacity, which is a key issue in the domestication process.

Effect of host factors and experimental conditions on the horizontal transmission of Enteromyxum leei (Myxozoa) to gilthead sea bream, Sparus aurata L., and European sea bass, Dicentrarchus labrax (L.) - A Sitjà‐Bobadilla; A Diamant; O Palenzuela; P Alvarez‐Pellitero (Journal of Fish Diseases, 2007)

Early development and growth of the laboratory reared north‐east Atlantic mackerel Scomber scombrus L. - D. Mendiola; P. Alvarez; U. Cotano; A. Martínezde Murguía (Journal of Fish Biology, 2007)
The early development, growth and morphological changes of mackerel Scomber scombrus were investigated at different incubation temperatures (8, 10, 13, 15 and 18° C). Details on the early life history are illustrated with special reference to morphological transformations. Culture techniques to rear larval mackerel stages are described using laboratory cultured foods. Artificially fertilized eggs were hatched after 80·6 h at 18·4° C and 256·8 h at 8·7° C. The standard length ( L S ) of the individuals at first feeding was 4·71 ± 0·18 mm. Four mortality critical periods and cannibalistic behaviour were identified. A maximum average larval size of 37·5 ± 4·41 mm L S was attained 30 days post‐hatch (dph) at 18·4° C. Development and growth were affected significantly by temperature during both endogenous and exogenous feeding periods. Larvae grew more rapidly at high, than at low temperatures. Daily specific growth rate (in mass) ranged from 2·4% at 10·6° C to 16·9% at 18·4° C. Likewise, average growth rate (in length) ranged from 0·05 mm day −1 at 8·4° C to 0·37 mm day −1 at 18·4° C. The allometric relationship of L S , with several body measurements was not affected by temperature. Comparison with larvae collected in the Bay of Biscay did not show any significant difference in the dry mass and L S relationship; conversely, the growth rate in length differed significantly between both laboratory and field conditions. The trends observed in the laboratory are described in relation to some aspects of the year‐class strength regulation.

Thermal effects on growth and time to starvation during the yolk‐sac larval period of Atlantic mackerel Scomber scombrus L. - D. Mendiola; L. Ibaibarriaga; P. Alvarez (Journal of Fish Biology, 2007)
The effect of incubation temperature (8·6, 11·1, 13·2, 15·1 and 16·8° C) on north‐east Atlantic mackerel Scomber scombrus development, growth and age at starvation during the yolk‐sac larval period was investigated. Standard length at hatch was found to be inversely proportional to incubation temperatures within the natural thermal ranges of this species; it ranged from 3·76 mm at 11·1° C to 3·30 mm at 17·8° C. Following hatch, however, larval growth rate was positively related to temperature. Individual logistic models, as a function of temperature and age, were fitted to the development processes of gape, eye pigmentation, jaw mobility and yolk exhaustion. Thereafter, development was classified into different ordered stages and an extended continuation model was fitted to the multinomial ordered stage classification. In all cases, there was a difference of >23 h between the first and the last individual developing in certain stage. The probability of survival decreased with age and was inversely related to temperature. Yolk utilization varied from 4·5 to 8·6 days and individuals died between 7·9 and 12·2 days from 17·8 to 11·1° C. The study demonstrated the significant impact that temperature has on development, growth and survival rates, during the early life history.

Characterisation and Variation of Morphological Traits and Storage Proteins in Spanish Emmer Wheat Germplasm (Triticum Dicoccon) - J.B. Alvarez; L. Caballero; P. Ureña; M. Vacas; L.M. Martín (Genetic Resources and Crop Evolution, 2007)

Sensitivity studies of the RegCM3 simulation of summer precipitation, temperature and local wind field in the Caribbean Region - D. Martínez-Castro; R. Porfirio da Rocha; A. Bezanilla-Morlot; L. Alvarez-Escudero; J. P. Reyes-Fernández; Y. Silva-Vidal; R. W. Arritt (Theoretical and Applied Climatology, 2006)

Identification of type-specific and cross-reactive neutralizing conformational epitopes on the major capsid protein of human papillomavirus type 31 - M. J. J. Fleury; A. Touzé; E. Alvarez; G. Carpentier; C. Clavel; J.-F. Vautherot; P. Coursaget (Archives of Virology, 2006)

Spatial Distribution, Scaling and Self-similar Behavior of Fracture Arrays in the Los Planes Fault, Baja California Sur, Mexico - A. F. Nieto-Samaniego; S. A. Alaniz-Alvarez; G. Tolson; K. Oleschko; G. Korvin; S. S. Xu; J. A. Prez-Venzor (Pure and Applied Geophysics, 2005)

β3-Adrenergic-dependent and -independent mechanisms participate in cold-induced modulation of insulin signal transduction in brown adipose tissue of rats - Alessandra L. Gasparetti; Fernanda Alvarez-Rojas; Eliana P. de Araujo; Aparecida E. Hirata; Mário J. A. Saad; Lício A. Velloso (Pflügers Archiv - European Journal of Physiology, 2005)

Application of Lead Isotopic Ratios in Atmospheric Pollution Studies in the Valley of Mexico - T. Martinez; J. Lartigue; F. Juarez; P. Avila-Perez; G. Zarazua; C. Marquez; M. P. Orta; V. Alvarez (Journal of Atmospheric Chemistry, 2004)

CD44 and hyaluronic acid regulate in vivo iNOS expression and metalloproteinase activity in murine air-pouch inflammation - P. V. Cabrera; G. Blanco; L. Alaniz; S. Greczanik; M. Garcia; E. Alvarez; S. E. Hajos (Inflammation Research, 2004)

Superior cervical ganglionectomy differentially modifies median eminence and anterior and mediobasal hypothalamic GABA content in male rats: effects of hyperprolactinemia - A.I. Esquifino; M.P. Alvarez; P. Cano; V. Jimnez; B. Duvilanski (Experimental Brain Research, 2004)

Removal of Explosives Using an Integrated Iron?Microbial Treatment in Flow-Through Columns - B.-T. Oh; P. J. Alvarez (Bulletin of Environmental Contamination and Toxicology, 2004)

Identification of quantitative trait loci involved in fruit quality traits in melon (Cucumis melo L.) - A. J. Monforte; M. Oliver; M. J. Gonzalo; J. M. Alvarez; R. Dolcet-Sanjuan; P. Arús (Theoretical and Applied Genetics, 2004)

FEEDING ECOLOGY OF THE MARINE OTTER ( LUTRA FELINA ) IN A ROCKY SEASHORE OF THE SOUTH OF CHILE - Gonzalo Medina‐Vogel; Claudio Delgado Rodriguez; P. Ricardo E. Alvarez; V. Jose Luis Bartheld (Marine Mammal Science, 2004)
A bstract The marine otter ( Lutra felina ) lives exclusively along exposed rocky shorelines on the South American Pacific coast from Peru (6°S), to Cape Horn, Chile (56°S), and Isla de los Estados, Argentina. L. felina diet and its relationship to prey availability and energy content was assessed by spraint and prey remains analysis, direct observation, and the use of crab pots and fish traps, at four sites on the Valdivian coast in the south of Chile, between June 1999 and June 2000. Based on spraints analysis, the diet was composed of 25 species; 52% (13/25) of the species identified were crustaceans, 40% (10/25) were fish, and 8% (2/25) were mollusks. Crustaceans were found in 78% of 475 spraints, 100% of 929 prey remains, and 90.8% of prey determined by direct observation, fish in 20% of spraints and 9.0% of prey determined by direct observation, and mollusks in 2% of spraints and 0.2% of prey determined by direct observation. Observed seasonal variation in prey availability was reflected in the otter diet. Fourteen prey species were trapped; 43% (6/14) were crustaceans and 57% (8/14) fish, crustaceans were 93% of 566 trapped individuals, fish 7%. L. felina showed opportunistic feeding behavior, selecting prey seasonally according to their availability rather than to their energy input.

Comparison of the influence of different elicitors on hyoscyamine and scopolamine content in hairy root cultures of Brugmansia candida - S. Pitta Alvarez; P. L. Marconi; A. Giulietti (In Vitro Cellular & Developmental Biology - Plant, 2003)

A strain isolated from gas oil‐contaminated soil displays chemotaxis towards gas oil and hexadecane - Mariana P. Lanfranconi; Héctor M. Alvarez; Claudia A. Studdert (Environmental Microbiology, 2003)
Summary In this report we describe the isolation of a strain from soil contaminated with gas oil by taking bacteria from a chemotactic ring on gas oil‐containing soft agar plates. Partial 16 S rDNA sequencing of the isolated strain showed 99.1% identity with Flavimonas oryzihabitans . It was not only able to degrade different aliphatic hydrocarbons but it was also chemotactic towards gas oil and hexadecane, as demonstrated by the use of three different chemotaxis methods, such as agarose plug and capillary assays and swarm plate analysis. In addition, the strain was chemotactic to a variety of carbon sources that serve as growth substrates, including glucose, arabinose, mannitol, glycerol, gluconate, acetate, succinate, citrate, malate, lactate and casaminoacids. This is the first report on chemotaxis of a hydrocarbon‐degrading bacterium towards a pure alkane, such as hexadecane. The fact that environmental isolates show chemotaxis towards contaminant/s present in the site of isolation suggests that chemotaxis might enhance biodegradation by favouring contact between the degrading microorganism and its substrate.

Voriconazole in the Treatment of Invasive Mold Infections in Transplant Recipients - J. Fortn; P. Martn-Dvila; M. A. Snchez; V. Pintado; M. E. Alvarez; A. Snchez-Sousa; S. Moreno (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Effects of overexpression of growth hormone on T cell activity in transgenic mice - A. I. Esquifino; A. Arce; M. P. Alvarez; A. Szary; H. Brown-Borg; A. Bartke (Journal of Physiology and Biochemistry, 2002)

Atmospheric dispersion, environmental effects and potential health hazard associated with the low-altitude gas plume of Masaya volcano, Nicaragua - P. Delmelle; J. Stix; P. Baxter; J. Garcia-Alvarez; J. Barquero (Bulletin of Volcanology, 2002)

Rat NKCC2/NKCC1 cotransporter selectivity for loop diuretic drugs - Hannaert P.; Alvarez-Guerra M.; Pirot D.; Nazaret C.; Garay R. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Genetic, morphological, and chemical divergence in the sponge genus Latrunculia (Porifera: Demospongiae) from New Zealand - Miller K.; Alvarez B.; Battershill C.; Northcote P.; Parthasarathy H. (Marine Biology, 2001)

Acidogenic fermentation of source separated mixtures of vegetables and fruits wasted from supermarkets - P. Traverso; P. Pavan; D. Bolzonella; L. Innocenti; F. Cecchi; J. Mata-Alvarez (Biodegradation, 2000)

Blue-light regulation of phytoene dehydrogenase ( carB ) gene expression in Mucor circinelloides - Antonio Velayos; José L. Blasco; María I. Alvarez; Enrique A. Iturriaga; Arturo P. Eslava (Planta, 2000)

5-HT 3 - and 5-HT 2C -antagonist properties of cyamemazine: significance for its clinical anxiolytic activity - M. Alvarez-Guerra; F. d'Alch-Bire; W. A. Wolf; F. Vargas; M. Dib; R. P. Garay (Psychopharmacology, 2000)

Silencing of HMW glutenins in transgenic wheat expressing extra HMW subunits - M. L. Alvarez; S. Guelman; N. G. Halford; S. Lustig; M. I. Reggiardo; N. Ryabushkina; P. Schewry; J. Stein; R. H. Vallejos (Theoretical and Applied Genetics, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Myxosporean infection causing intestinal disease in farmed turbot, Scophthalmus maximus (L.), (Teleostei: Scophthalmidae) - E. Branson; A. Riaza; P. Alvarez‐Pellitero (Journal of Fish Diseases, 1999)
The present report describes an intestinal disease which causes important losses in farmed turbot. Mortality rates were higher in summer and reached 100% in all tanks where the disease was confirmed. Affected fish showed external signs consisting of anorexia, sunken eyes and a typical prominent bony ridge on the skull. These signs can be considered the pathognomonic signs of the disease, together with the gut lesions seen in the histological study. Pallor of the internal organs, intestinal haemorrhages and the presence of liquid in the intestine were also observed, with ascites in heavily infected fish. Histopathological damage was evident in the gut, with severe enteritis, detachment of epithelium, haemorrhages and inflammation of the subepithelial connective tissue. The myxosporean aetiology was demonstrated in all the fish showing the characteristic signs of disease. Myxosporean stages, including scarce spores, were found in the affected epithelium or free in the intestinal lumen together with epithelial debris. The present study demonstrates the importance of this myxosporean disease which represents a serious threat for turbot culture. This is also the first record of a member of the Myxosporea in turbot.

Bacterial and parasitic pathogens in cultured common dentex, Dentex dentex L. - R Company; A Sitj; M J Pujalte; E Garay; P Alvarez‐Pellitero; J P (Journal of Fish Diseases, 1999)
A bacteriological and parasitological study on cultured common dentex, Dentex dentex L., was conducted in a 2‐year survey. Two different groups of fish were studied: (1) sampled only when mortalities occurred; and (2) sampled periodi‐cally from 10 days post‐hatch until the juvenile stage. In both groups, peaks of mortalities coincided with high water temperatures. The same parasites were detected in both groups, except Ichthyophonus sp., which was identified only in the trunk kidney of fish from group 1. Two myxosporeans, Ceratomyxa sp. and Lepthotheca sp., were found in the bile and the trunk kidney, respectively. Epitheliocystis infection was also very frequent in the gills. An unidentified microsporidium, which was found in the liver, occurred very infrequently. Vibrio harveyi was dominant in samples from diseased animals (79%) and clearly associated with mortalities. It was not detected in water or larval homogenates. A high percentage (60%) of the isolates of this species were sorbitol positive. Other less frequently occurring bacteria were V. alginolyticus and Photobacterium (V.) damselae. The disease conditions found in common dentex were considered to be multifactorial in origin.

Increased Activity of Wall Hydrolytic Enzymes May Explain the Phenotype of Saccharomyces cerevisiae Fragile Mutants - José Ruiz-Herrera; Claudia León-Ramírez; P. Elizabeth Alvarez; Pencho Venkov (Current Microbiology, 1998)

Prospective Study of Streptococcus milleri Hepatic Abscess - J. Corredoira; E. Casariego; C. Moreno; L. Villanueva; M. J. López Alvarez; J. Varela; A. Rodríguez; P. Alonso; A. Coira (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Prospective study ofStreptococcus milleri hepatic abscess - J. Corredoira; E. Casariego; C. Moreno; L. Villanueva; M. J. López Alvarez; J. Varela; A. Rodríguez; P. Alonso; A. Coira (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Phenotypic variability in different strains of Pseudomonas syringae subsp. savastanoi isolated from different hosts - F. Alvarez; J.E. García de los Ríos; P. Jimenez; A. Rojas; P. Reche; M.T. Troya (European Journal of Plant Pathology, 1998)

Characterization of phenotypically distinct strains of Xanthomonas axonopodis pv. citri from Southwest Asia - C. Vernière; J.S. Hartung; O.P. Pruvost; E.L. Civerolo; A.M. Alvarez; P. Maestri; J. Luisetti (European Journal of Plant Pathology, 1998)

Towards the prediction of rock excavation machine performance - H. J. R. Deketh; M. Alvarez Grima; I. M. Hergarden; M. Giezen; P. N. W. Verhoef (Bulletin of Engineering Geology and the Environment, 1998)

The level of erbB2 expression predicts sensitivity to the cytotoxic effects of an intracellular anti-erbB2 sFv - J. Grim; Jessy Deshane; Gene P. Siegal; Ronald D. Alvarez; Paolo DiFiore; D. T. Curiel (Journal of Molecular Medicine, 1998)

Variation in the nuclear ribosomal DNA internal transcribed spacer (ITS) region of Pinus rzedowskii revealed by PCR-RFLP - A. Quijada; A. Liston; P. Delgado; A. Vázquez-Lobo; E. R. Alvarez-Buylla (Theoretical and Applied Genetics, 1998)

Pax-2 in the chiasm - G. Alvarez-Bolado; M. Schwarz; P. Gruss (Cell and Tissue Research, 1997)

Ichthyophonus infections in cultured marine fish from Spain - A. Franco‐Sierra; A. Sitj́a‐Bobadilla; P. Alvarez‐Pellitero (Journal of Fish Biology, 1997)
Ichthyophonus sp. is reported for the first time in Mugil capito (thinlip grey mullet) and Li a saliens (leaping grey mullet). The fungus was also found in L. aurata (golden grey mullet), Dicentrarchus labrax (sea bass), Sparus aurata (gilthead sea bream) and Scophthalmus maximus (turbot), whereas Mugil cephalus (grey mullet) was not parasitized. In fish sampled periodically, the highest prevalences were observed in sea bass and the lowest in turbot. Among the fish sampled occasionally, the fungus was found associated to an epizootic in thinlip grey mullet. Ichthyophonus was never found in fish weighing Ichthyophonus sp. parasitized different organs of thinlip and leaping grey mullets, though infection intensity was maximal in the spleen. In the remaining fish, the fungus was found mainly in the trunk kidney, where it appeared frequently in a necrotic form. Ichthyophonus sp. can be considered a potential threat for marine fish aquaculture, especially in culture conditions which may favour the introduction and transmission of the fungus.

A new HLA-G allele ( HLA-G * 0105N ) and its distribution in the Spanish population - M. B. Suárez; P. Morales; M. José Castro; Víctor Fernández; Pilar Varela; Miguel Alvarez; Jorge Martínez-Laso; A. Arnaiz-Villena (Immunogenetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Immobilized Lotus tetragonolobus agglutinin binds oligosaccharides containing the Lex determinant - Liying Yan; Patricia P Wilkins; Gerardo Alvarez-Manilla; Su-Il Do; David F Smith; Richard D Cummings (Glycoconjugate Journal, 1997)

Biologia deMeteorus rubens (Hym.: Braconidae), parasitoide primario deAgrotis ipsilon (Lep.: Noctuidae) - P. Caballero; E. Vargas-Osuna; C. Santiago-Alvarez (BioControl, 1992)